2014
DOI: 10.1124/mol.114.095539
|View full text |Cite
|
Sign up to set email alerts
|

Neurotransmitter GABA Activates Muscle but Notα7 Nicotinic Receptors

Abstract: Cys-loop receptors are neurotransmitter-activated ion channels involved in synaptic and extrasynaptic transmission in the brain and are also present in non-neuronal cells. As GABA A and nicotinic receptors (nAChR) belong to this family, we explored by macroscopic and single-channel recordings whether the inhibitory neurotransmitter GABA has the ability to activate excitatory nAChRs. GABA differentially activates nAChR subtypes. It activates muscle nAChRs, with maximal peak currents of about 10% of those elicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
1
1
0
Order By: Relevance
“…This may mean that much of the acute pain response evoked by glutamate when injected into the human masseter muscle is coded by the firing of Aδ afferent fibers and thus that GABA, through its stronger depolarizing action on myelinated fibers acts to increase pain intensity reports. A recent report also indicated that GABA has the ability to activate neuromuscular nicotinic receptors at high concentration, which could lead to low level muscle contraction [32]. In the present study, subjects commonly reported that the muscle felt tight after GABA and glutamate were co-injected.…”
Section: Discussionsupporting
confidence: 52%
“…This may mean that much of the acute pain response evoked by glutamate when injected into the human masseter muscle is coded by the firing of Aδ afferent fibers and thus that GABA, through its stronger depolarizing action on myelinated fibers acts to increase pain intensity reports. A recent report also indicated that GABA has the ability to activate neuromuscular nicotinic receptors at high concentration, which could lead to low level muscle contraction [32]. In the present study, subjects commonly reported that the muscle felt tight after GABA and glutamate were co-injected.…”
Section: Discussionsupporting
confidence: 52%
“…Several nAChR ligands possess an affinity toward γ-aminobutiric acid receptors (GABA A R) and vice versa: d -tubocurarine and α-cobratoxin act on GABA A R with sub-micromolar affinity [ 23 ], bicuculline inhibits α9 nAChR [ 24 ], and even GABA itself activates muscle nAChR [ 25 ]. Therefore, testing MG action on GABA A R was an essential part of this study.…”
Section: Resultsmentioning
confidence: 99%